Prevalence and predictors of potentially inappropriate medication use among ambulatory older adults in Northern Nigeria - Abubakar, Usman; Tangiisuran, Balamurugan; Kolo, Mohammad; Yamma, Abdulkadir Ibrahim; Hammad, Mohamed Anwar; Sulaiman, Syed Azhar (Springer Nature, 2020)
Objectives There is a paucity of data describing the prevalence of and factors associated with the use of potentially inappropriate medications (PIMs) among older adults in Northern Nigeria. This study evaluates the prevalence and predictors of PIMs used among older adults attending outpatient clinics. Methods This cross-sectional study involved patients aged ≥ 65 years attending outpatient clinics in two public hospitals and was conducted from June to September 2016. PIMs were detected using the American Geriatrics Society (AGS) 2015 updated Beers criteria and the Screening Tool of Older People’s potentially inappropriate Prescriptions (STOPP) [version 2] criteria. Results A total of 244 older adults (mean age 71.1 ± 6.1 years) were included. The prevalence of PIM measured using Beers (67.2%) and STOPP criteria (40.2%) varied signifcantly (p = 0.047). Both Beers and STOPP criteria identifed at least one PIM in 73 patients (29.9%). Nonsteroidal anti-infammatory drugs (NSAIDs) and α-methyldopa were the most common PIMs identifed using the Beers criteria. Concurrent use of an angiotensin-converting enzyme inhibitor and amiloride was observed in 32.4% of older adults. “Glibenclamide and glimepiride” and “NSAIDs with concurrent antiplatelet without proton pump inhibitor” were the most common PIMs detected by the STOPP criteria. The number of medications being taken and the hospital attended were signifcant predictors of PIM. Conclusion The prevalence of PIMs among ambulatory older adults was relatively high. A higher number of medications and the hospital attended were associated with a greater risk of PIMs. The 2015 Beers criteria detected signifcantly higher PIMs than the STOPP criteria (version 2). These observations highlight the need for interventions to improve the use of medications in older adults.